Peacebuilding and Social Work: The Narratives of Community Organizers in Conflict-Affected Areas in Maguindanao - Princess Sheryn Mamucao (RIRAI Publisher, 2022)
This study aimed to determine the challenges experienced by the social workers as community organizers in peacebuilding-related community organizing in armed conflict-affected areas in Maguindanao. It sought to know the peacebuilding initiatives of the community organizers in community organizing and the experiences encountered by the community organizers in peacebuilding–related community organizing and in working with conflict-affected areas. Phenomenological method of qualitative research was used. The participants were community organizers working in Community and Family Services International (CFSI) and Ministry of Social Services and Development (MSSD) - Maguindanao. Purposive sampling was used in identifying the target participants. Findings show that community organizing contributes to promoting peacebuilding in the conflict-affected areas through the programs and services being implemented by the community organizers by conducting Family Development Sessions which fosters family development, promotes healthy family life, responsible parenthood, parent effectiveness, cultural solidarity, and environmental awareness. Peacebuilding does not only revolve around initiatives at the macro level but starting in advocacy in responsible parenthood and parent effectiveness could lead to the prevention of peace-related issues and community problems. It is concluded that the participation of the people is the major challenge encountered by the community organizers. The peace and order situation of the community is also vital in the successful flow of the community organizing process. KEYWORDS Peacebuilding, Social Work, Community Organizing, Community Organizer, Conflict-affected areas